(3GdEQTGO deUGdM GdCfaS hGdCLSGOs - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s
(3ChdgG (B:s
(3Efg deG cGf GdeLdS GdSGei GdCLdi hVefJg ef CUhdgG haQhYgG eG JVefJg GdcJH GdcHGQ hbSeJg CQHY ebGdGJ s
(3BNQgG (B:s
(3GdedYbI eYdbJGf , eYdbI GdYSd hgj CQHYI eKGbjd , heYdbI GdCOhjI hgj eKbGd hGMO JeJ GdebGdg GdQGHYI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B18 s
(3eUOQ GbJfGA GdCUd (B:s
(3jfi LGeY HESJGfHhd (B(912) s
Keywords: (3GdWHs